Analysis Of Medical Health Equipment Treatment At Royal Prima Medan General Hospital - Actor Martin Oloan S; Chrismis Novalinda Ginting; Rapael Ginting (International Journal of Health and Pharmaceutical (IJHP), 2022)
Medical devices are one of the factors that play an important role in providing health services to the community. Sustainable health services need to be supported by equipment that is always in a ready-to-use condition and can function properly. The level of public health needs to be improved through quality health services, one of which is through the provision of good, safe and suitable medical devices. So that medical equipment is always in good condition, safe, and suitable for use, it is necessary to carry out preventive maintenance including periodic maintenance and implementation of tests and calibrations. The purpose of this study was to analyze the Treatment of Medical Medical Devices at Royal Prima Hospital Medan. The results of this study indicate that the number of human resources in carrying out medical device maintenance at Royal Prima Hospital Medan is maximized, the exact amount of funds for the maintenance of medical devices at Royal Prima Hospital Medan is unknown, but each device already has its own budget in terms of treatment. and repairs, the placement of medical devices, especially in the ICU and IGD rooms, is in accordance with SOPs, it can be seen that their placement is regular and easy to reach by health workers such as doctors and nurses, the maintenance of medical devices is routinely carried out as well as once a week technicians always carry out maintenance on medical devices, supervision has also been carried out optimally by technicians if there are medical devices that are constrained in their operation.